2004
DOI: 10.1177/000348940411300604
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Young Adults Who Had Ventilation Tube Insertion in Childhood

Abstract: It is known that insertion of ventilation tubes can cause damage to the tympanic membrane and hearing deterioration in the long-term. To investigate long-term effects of recurrent otitis media and of ventilation tube insertion, we used a study group (n = 358 subjects), with or without a history of otitis media and/or ventilation tube insertion, derived from a birth cohort that had been followed for 16 years. At 18 years of age, a standardized audiometric and otoscopic examination was performed. We found that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 16 publications
2
40
1
Order By: Relevance
“…Moreover, the sensitivity at different frequencies between 0.25 and 8.0 kHz fell within the normal agerelated values. 13,14 Among children with OM, de Beer et al 15 found hearing levels to be worse in those with than without VT treatment at the ages of 8 and 18 years. The association of VTs with the observed hearing loss is difficult to evaluate because of the heavier disease load in the patients with VT treatment.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the sensitivity at different frequencies between 0.25 and 8.0 kHz fell within the normal agerelated values. 13,14 Among children with OM, de Beer et al 15 found hearing levels to be worse in those with than without VT treatment at the ages of 8 and 18 years. The association of VTs with the observed hearing loss is difficult to evaluate because of the heavier disease load in the patients with VT treatment.…”
Section: Commentmentioning
confidence: 99%
“…The association of VTs with the observed hearing loss is difficult to evaluate because of the heavier disease load in the patients with VT treatment. In addition, de Beer et al 15 reported elevated BC thresholds among patients with VT treatment, with an increase between 8 and 18 years of age. We did not notice any significant sensorineural hearing loss or its progression, with the mean PTAs for BC of healed ears being −0.6 dB and 0.2 dB at 6 and 15 years of age, respectively.…”
Section: Commentmentioning
confidence: 99%
“…Insertion of tubes is the most frequently performed surgical procedure for children under 15 years of age in the USA, carried out more than 500,000 times in 1996 [1] . Although tympanostomy tubes are safe and effi cacious for most children with refractory otitis media, several sequelae may occur, including otorrhea, cholesteatoma, chronic perforation and hearing deterioration in the long term [2,3] . These problems associated with ventilation tubes encouraged otolaryngologists to fi nd alternative procedures for ventilation of the middle ear.…”
Section: Introductionmentioning
confidence: 99%
“…Quite a few studies indicate that longstanding SOM, even when treated, leads to poorer hearing after active disease has subsided [1][2][3][4][5][6][7][8][9][10]. Some of these studies concern extended high frequency audiometry and show losses mainly in the extended high frequency range [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies concern extended high frequency audiometry and show losses mainly in the extended high frequency range [1,3,4]. Reported hearing losses in the conventional frequency range are small [1][2][3][5][6][7][8][9][10][11]. Difficulties in hearing distorted speech have also been reported [1].…”
Section: Introductionmentioning
confidence: 99%